Determination of Chloride Levels in Water from PDAM Semanggi 2 and Cinere Well Water, South Tangerang Using Precipitation Titration with the Method MOHR - Nurhasni; Putri Anjeli; Regita Cahya Prameswari; Elita Delia Althaf; Medina Sheril Fatamizzihar (Journal of Engineering Science and Technology Management, 2026)
The Mohr method of argentometric precipitation titration is often used for chloride analysis in water due to its high accuracy and simplicity of procedure. This study aims to determine chloride levels in water from PDAM Semanggi 2 and well water from Cinere, South Tangerang. An experimental quantitative approach was applied to the Ciputat domestic water source population and 50 mL purposive samples from both locations on November 6, 2025. Instruments included a brown burette, a graduated pipette, an analytical balance, and AgNO3, NaCl, and K2CrO4; data analysis used normality calculations and average duplo. The results showed that the chloride levels in PDAM Semanggi 2 water were 80.02 mg/L and in Cinere well water were 92.34 mg/L, both below the quality standard of 300 mg/L (PP No. 22/2021). It was concluded that well water has higher levels due to geological factors, so both sources are safe for domestic consumption with recommendations for regular monitoring.